Nanoscale electrostatic control in ferroelectric thin films through lattice chemistry - Ipek Efe; Alexander Vogel; William S. Huxter; Elzbieta Gradauskaite; Iaroslav Gaponenko; Patrycja Paruch; Christian L. Degen; Marta D. Rossell; Manfred Fiebig; Morgan Trassin (Nature Communications)
Abstract Nanoscale electrostatic control of oxide interfaces enables physical phenomena and exotic functionalities beyond the realm of the bulk material. In technologically-relevant ferroelectric thin films, the interface-mediated polarization control is usually exerted by engineering the depolarizing field. Here, in contrast, we introduce polarizing surfaces and lattice chemistry engineering as an alternative strategy. Specifically, we engineer the electric-dipole ordering in ferroelectric oxide heterostructures by exploiting the charged sheets of the layered Aurivillius model system. By tracking in-situ the formation of the Aurivillius charged Bi2O2 sheets, we reveal their polarizing effect leading to the characteristic Aurivillius out-of-plane antipolar ordering. Next, we use the polarizing Bi2O2 stacking as a versatile electrostatic environment to create new electric dipole configurations. We insert multiferroic BiFeO3 into the Aurivillius framework to stabilize a ferrielectric-like non-collinear electric-dipole order in the final heterostructure while maintaining the antiferromagnetic order of BiFeO3. We thus demonstrate that engineering the lattice chemistry stabilizes unconventional ferroic orderings at the nanoscale, a strategy that may be expanded beyond the realm of electrically ordered materials.